Capacity building and predictors of success for HIV‐1 drug resistance testing in the Asia‐Pacific region and Africa. Issue 1 (10th July 2013) - Land, Sally; Zhou, Julian; Cunningham, Philip; Sohn, Annette H; Singtoroj, Thida; Katzenstein, David; Mann, Marita; Sayer, David; Kantor, Rami
Abstract : Background: The TREAT Asia Quality Assessment Scheme (TAQAS) was developed as a quality assessment programme through expert education and training, for laboratories in the Asia‐Pacific and Africa that perform HIV drug‐resistance (HIVDR) genotyping. We evaluated the programme performance and factors associated with high‐quality HIVDR genotyping. Methods: Laboratories used their standard protocols to test panels of human immunodeficiency virus (HIV)‐positive plasma samples or electropherograms. Protocols were documented and performance was evaluated according to a newly developed scoring system, agreement with panel‐specific consensus sequence, and detection of drug‐resistance mutations (DRMs) and mixtures of wild‐type and resistant virus (mixtures). High‐quality performance was defined as detection of ≥95% DRMs. Results: Over 4.5 years, 23 participating laboratories in 13 countries tested 45 samples (30 HIV‐1 subtype B; 15 non‐B subtypes) in nine panels. Median detection of DRMs was 88–98% in plasma panels and 90–97% in electropherogram panels. Laboratories were supported to amend and improve their test outcomes as appropriate. Three laboratories that detected <80% DRMs in early panels demonstrated subsequent improvement. Sample complexity factors – number of DRMs ( p <0.001) and number of DRMs as mixtures ( p <0.001); and laboratory performance factors – detection of mixtures ( p <0.001) and agreement with consensus sequence ( p <0.001), were associated with high performance; sample format (plasma or electropherogram), subtype and genotyping protocol were not. Conclusion: High‐quality HIVDR genotyping was achieved in the TAQAS collaborative laboratory network. Sample complexity and detection of mixtures were associated with performance quality. Laboratories conducting HIVDR genotyping are encouraged to participate in quality assessment programmes.